Insights into the coordination sphere of copper ion in polymers containing carboxylic acid and azole groups - Lazaro Martinez, Juan Manuel (2013)
In this work, we describe the Cu2+ ion uptake from recently developed hydrogel with polyampholyte and polyelectrolyte behavior at different concentrations of the metal ion. Solid-state NMR and EPR were used as complementary techniques to understand the coordination role of carboxylic acid and azole groups (imidazole, triazole and pyrazole) involved in the copper ion coordination. In polymers containing imidazole and triazole, the uptake took place preferentially through the azole groups, with less participation of the carboxylate groups at low concentrations of Cu2+. However, as the concentration of Cu2+ increased, these azole ligands became less active in the new sites for copper. In polymers containing pyrazole, coordination of Cu2+ was through both carboxylate and pyrazole ligands, regardless of the concentration of Cu2+ . Interactions of the different ligands in the networks and the structural changes produced by copper ions (Cu1+, Cu2+) were characterized by thermal and NMR measurements.